The Feros - King, Wesley (G.P. Putnam's Sons, 2013)
"James, Hayden, Lana, Sam and Emily use their new superpowers to try to save abducted members of the League of Heroes, and when Emily disappears, they must find their friend before it's too late"--Provided by publisher.